IMPLEMENTATION OF WOMEN'S PROTECTION FOR VICTIMS OF SEXUAL VIOLENCE IN CIREBON REGENCY - Icha Rahma Nurul Afni; Moh. Sigit Gunawan (Fakultas Hukum Universitas Swadaya Gunung Jati, 2026)
Sexual violence against women is a serious problem that continues to increase and requires special attention from various parties, especially local governments. This study aims to analyze the implementation of legal protection for women victims of sexual violence in Cirebon Regency and identify factors that affect the effectiveness of its implementation. The research method used is an empirical juridical approach with data collection methods through interviews, observations, and documentation research on relevant institutions, such as the police, women and child protection institutions, and victims The research results show that the implementation of protection for victims has been carried out through various efforts, such as legal assistance, health services, psychological rehabilitation, and the provision of safe houses. However, its implementation still faces various obstacles, including limited resources, a lack of coordination between institutions, and low public awareness in reporting cases of sexual violence. In addition, cultural factors and social stigma also hinder victims from obtaining optimal protection. In conclusion, the implementation of the protection of women victims of sexual violence in Cirebon Regency has not been running optimally. Therefore, it is necessary to increase institutional synergy, strengthen human resources capacity, and educate the public to create a more effective and fairer protection system for victims.